Valuing the diverse economies and climate possibilities of a winter festival in Western Maine, USA - Matthew McCourt; Gabriel Perkins (IdeAs)
A group of citizens in western Maine was recently galvanized by their shared, volunteer labor of preparing a course for a major regional ski race during a low snow season. Working late into the night they shoveled snow by hand from the woods to the race course, paving the way for the success of the event, as well as animating subsequent efforts to use winter sports to build a diverse economy. Shortly after rescuing the race from a warm spell, the citizens group successfully planned and hosted a larger regional ski festival. Their follow-up festival incorporated an experiment in a walkable/skiable event venue with shuttle buses providing transportation to lodging and off-site parking for day trippers. In keeping with the diverse economies framework (Gibson-Graham 2006, 2008), festival organizers worked with researchers to estimate the value of their own volunteer labor, in addition to measuring the emitted and avoided CO2 resulting from their mitigation practices. This paper shares the results of the festival study while documenting how a particular instance of community labor bridges different interests, performs diverse economies and enacts a “climate politics of hope” in the face of climate uncertainty.